How do Chinese people evaluate “Tang-Ping” (lying flat) and effort-making: The moderation effect of return expectation - Hsu, Han-Yu (Frontiers in Psychology, 2022)
"Tang-Ping" (TP), referring to "lying flat" literally, has been a buzzword in China web media since 2021. As the opponent of Effort-Making (EM) behaviors which have both instrumental and purpose values in Confucian culture, TP has a negative moral implication in China and has been criticized by the state-owned media. Meanwhile, the meaning of TP also contains a negative form of resistance towards social and organizational inequality, which may be acceptable under unfair circumstances. This study employed the imagined-scenario method to investigate the public's moral evaluations of TP and EM behaviors under conditions of different return expectations. An online questionnaire with 2 (TP vs. EM) by 2 (low vs. high return expectation) between-participants designed scenarios was employed, along with the measurements of Obligation Belief of Effort (OBE) and Improvement Belief of Effort (IBE) scales (N = 210). The results found that 1) TP behaviors were evaluated morally wrong in general, while EM behaviors were morally right; 2) the return expectation of scenario moderated the behavior type's effect on moral evaluation, that EM behaviors were evaluated positively regardless of return expectation, while TP behaviors became acceptable with a neutral score under the low return expectation; 3) both OBE and IBE correlated positively with evaluations of EM while negatively with evaluations of TP. The theoretical and practical implications were discussed.